Ecological Risk Assessment for Chlorpyrifos in Terrestrial and Aquatic Systems in the United States - Giesy, John P.; Solomon, Keith R. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews, 2014)
CONTENTS Preface Foreword by Keith Solomon and John Giesy Foreword by Coordinating Board of Editors Ecological Risk Assessment of the Uses of the Organophosphorus Insecticide Chlorpyrifos, in the United States John P. Giesy, Keith R. Solomon, G. Christopher Cutler, Jeffrey M. Giddings, Don Mackay, Dwayne Moore, John Purdy, W. Martin Williams Properties and Uses of Chlorpyrifos in the United States Keith R. Solomon, W. Martin Williams, Donald Mackay, John Purdy, Jeffrey P Giddings, John P. Giesy Fate in the Environment and Long-Range Atmospheric Transport of the Organophosphorus Insecticide, Chlorpyrifos and its Oxon Don Mackay, John P.Giesy, Keith R.Solomon Exposures of Aquatic Organisms to the Organophosphorus Insecticide, Chlorpyrifos Resulting from Use in the United States W. Martin Williams, Jeffrey M Giddings, John Purdy, Keith R Solomon, John Giesy Risks to Aquatic Organisms from Use of Chlorpyrifos in North America Jeffrey M. Giddings, W. Martin Williams, Keith R. Solomon, John P. Giesy Refined Avian Risk Assessment for Chlorpyrifos Dwayne R.J. Moore, R. Scott Teed, Colleen D. Greer, Keith R. Solomon, and John P. Giesy Risk to Pollinators from the Use of Chlorpyrifos in North America G. Christopher Cutler, John Purdy, John P. Giesy, and Keith R. Solomon Index.